The Hidden Role of Twitter Users in Social Policy as an Agenda-Setting Tool: The Case of Yemeksepeti and Migros - Bilal Coşan (İstanbul İktisat Dergisi)
Media is an important agenda setting tool. With the development of Web 2.0 technologies in particular, many issues related to daily life have come to the agenda regarding social media. In this context in terms of social policy, the employer/employee relations and problems of other disadvantaged groups have also been able to come to the agenda on Twitter. As an important social policy actor, civil society also plays an active role in shaping social policies on the Web both in a narrow and broad sense. The aim of this study is to discuss the hidden role of Twitter users regarding social policies as an agenda-setting tool. This study evaluates how Twitter users have interpreted the wage raise struggle of Yemeksepeti motor couriers and Migros warehouse employees, which started in the beginning of February 2022 and lasted for more than a week. The study performs qualitative data analyses using the program MAXQDA. As a result, the majority of Twitter users’ tweets can be said to support employees’ social and economic rights.